Origin and classification of cultivated plants in Asháninka mythical thought - Rojas Zolezzi, Enrique (1997)
This article constitutes a first approach to the study of the classification criteria underlying the taxonomies of cultivated plants of the Campa Asháninka society of the central Peruvian Amazon. This text constitutes a first advance of a broader research about the conceptions on the relationships between this human group and the living beings of its environment, conceptual elements that play a fundamental role in the framework of production in neolithic technology societies such as the one studied here.